Tuning Antibody Presentation to Enhance T-Cell Activation for Downstream Cytotoxicity - Campbell, Elizabeth A (Langmuir : the ACS journal of surfaces and colloids, 2021)
Cytotoxic effector cells are an integral component of the immune response against pathogens and diseases such as cancer and thus of great interest to researchers who wish to enhance the native immune response. Although researchers routinely use particles to stimulate cytotoxic T cells, few studies have comprehensively investigated: (1) beyond initial activation responses (i.e., proliferation and CD25/CD69 expression) to downstream cancer-killing effects and (2) how to drive cytotoxic T-cell responses by adjusting biomolecular and physical properties of particles. In this study, we designed particles displaying an anti-CD3 antibody to activate cytotoxic T cells and study their downstream cytotoxic effects. We evaluated the effect of antibody immobilization, particle size, molecular surface density of an anti-CD3 antibody, and the inclusion of an anti-CD28 antibody on cytolytic granule release by T cells. We found that immobilizing the anti-CD3 antibody onto smaller nanoparticles elicited increased T-cell activation products for an equivalent delivery of the anti-CD3 antibody. We further established that the mechanism behind increased cancer cell death was associated with the proximity of T cells to cancer cells. Functionalizing particles additionally with the anti-CD28 antibody at an optimized antibody density caused increased T-cell proliferation and T-cell binding but we observed no effective increase in cytotoxicity. Meaningfully, our results are discussed within the context of commercially available and widely used anti-CD3/28 Dynabeads. These results showed that T-cell activation and cytotoxicity can be optimized with a molecular presentation on smaller particles and thus, offer exciting new possibilities to engineer T-cell activation responses for effective outcomes